Alex Drace-Francis, Istoria mămăligii. Povestea globală a unui preparat naţional [The Making of Mamaliga. Transimperial Recipes for a Romanian National Dish], transl. Anca Bărbulescu (București: Humanitas, 2023), 290 pages - MÂRZA, Radu (Studia Universitatis Babeș-Bolyai Historia, 2025)
Alex Drace-Francis is an Anglo-Scottish historian from the University of Amsterdam, who has been familiar with the Romanian space for several decades. He has an intimate knowledge of its literature and culture. Going through his publications, Alex Drace-Francis seems to have discovered it as a result of his broader concerns regarding the South-East European and Balkan space. In reality, he has known the Romanian space, from the perspective of cultural history, for more than 25 years, as his doctoral thesis, defended at the University of London in 2001, is called Literature, Modernity, Nation. The Case of Romania, 1829-1890. The thesis was published as a book a few years later: The Making of Modern Romanian Culture. Literacy and the Development of National Identity (I.B. Tauris, 2005), in several editions, intone of which was the Romanian translation (by Marius-Adrian Hazaparu): Geneza culturii române moderne. Instituţiile scrisului şi dezvoltarea identităţii naţionale. 1700-1900 (Polirom, 2016). It is one of several important works published in recent decades on this topic.